Rapid Plant Regeneration and Molecular Assessment of Genetic Stability Using ISSR and RAPD Markers in Commercial Banana Cv. Grand Naine (G-9) - DUHAN, J. S.; Kajla, S.; Choudhary, D.; Poonia, A. K. (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
The investigation was carried out to assess the genetic stability in tissue culture raised plants of banana cv. G-9 using random amplified polymorphic DNA (RAPD) and inter simple sequence repeats (ISSR) markers. Aims: Molecular assessment of genetic stability of tissue culture raised plants of banana cv. G-9 using molecular markers. Material and Results: Apical shoots were established on medium EM4 (MS + BAP 4.0 mg L-1) with maximum of 3.8 buds/explant in 2.6 days. The maximum bud multiplication with 16.5±0.06 shoots was observed on medium Ma3 (MS medium+ 5.0 mg L-1 BAP + 0.25 mg L-1NAA of + 30 mg L-1AdSO4). The maximum rooting response (100%) was observed on 1/2 MS medium supplemented with 2.0 mg L-1 NAA in 12.2 days. After acclimatization the hardened plants were examined for genetic stability using RAPD and ISSR primers. Total forty six (twenty six RAPD and twenty ISSR) markers were used. RAPD primers produced 87 distinct and scorable bands, with an average of 3.34 bands per primer and the amplification products range was from 100-1200 bps. The number of scorable bands for RAPD primer varied from 2 to 5 with an average of 3.34 bands per primer. ISSR primers produced 71 distinct and scorable bands in the range of 100-1000 bps and the number of scorable bands for each primer varied from 2 to 6 with an average of 3.55 bands per primer. Conclusion: Similar profile with monomorphic bands was observed for all the tissue culture raised plants when compared to mother plant in both types of markers used. The results corroborate the fact that plant tissue culture technology has immense importance for production of true to type of planting material.